Pharmaceuticals oxidation by chlorine and byproducts formation in aqueous matrices in bench scale - de Souza, Brígida P. [UNESP]; Lima, Diego R. S.; de Aquino, Sérgio F.; Quaresma, Amanda V.; Baêta, Bruno E. L.; Libânio, Marcelo (FapUNIFESP (SciELO), 2018)
Pharmaceuticals and endocrine disrupting compounds are found in Brazilian natural waters, including some water sources for public supply, also due to the low coverage of sewage collection and treatment in Brazil. This study investigated the removal of three pharmaceutical compounds — sulfamethoxazole (SMX), diclofenac (DCF) and 17β-estradiol (E2) — from aqueous solutions by means of chlorine oxidation (sodium hypochlorite) by varying the dose of chlorine and contact time in batch tests. The chlorine solutions were examined by chromatography attached to the mass spectrometry in order to identify the oxidation by-products. For 10 min contact time, mean removal values of 61% were observed for DCF; 36% for E2; and 33% for SMX, when the chlorine dose was 1.5 mg L-1. Just for DCF there was a statistically significant difference (α=0.05) in the removal efficiency when increasing the chlorine dose to 3.0 mg.L-1. The oxidation followed the kinetic model of pseudo-second order, with k2 values of 0.0168 L.μg.min-1 for SMX (at both chlorine doses tested); 0.0133 and 0.0798 L.μg.min-1 to DCF; and 0.0326 and 0.0289 L.μg.min-1 to the E2 at chlorine doses of 1.5 and 3.0 mg L-1, respectively. Finally, it was verified that an increase of the contact time favored the oxidation of all pharmaceuticals tested, although with the perspective of by-products formation for SMX and E2.
Oxidação de fármacos por cloro e formação de subprodutos em amostras aquosas em escala de bancada
Keywords: Disinfection; Endocrine disrupting compounds; Organic microcontaminants; Pharmaceuticals; Water treatment